2016
DOI: 10.4238/gmr.15027817
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for advanced glycation end-products (RAGE) is overexpressed in human osteosarcoma and promotes the proliferation of osteosarcoma U-2OS cells in vitro

Abstract: ABSTRACT. Osteosarcoma (OS) is an aggressive cancer of the long bones, and usually affects children and young adults. The receptor for advanced glycation end-products (RAGE) has recently been recognized as an oncogenic receptor that binds to different ligands, and promotes the progression of various cancers. However, little is known about the association between RAGE and the pathogenesis of OS. In this study, we first examined the expression of RAGE in OS tissues using immunohistochemical staining, western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…Therefore, growth factors, such as transforming growth factor (TGF), are deemed to be involved in the pathogenesis of OS due to the acceleration of OS cell proliferation and oncogenesis [Zhang, 2016]. A study has reported TGF-b1 could induce epithelial to mesenchymal transition (EMT) in lung cancer cells [Jo et al, 2015].…”
mentioning
confidence: 99%
“…Therefore, growth factors, such as transforming growth factor (TGF), are deemed to be involved in the pathogenesis of OS due to the acceleration of OS cell proliferation and oncogenesis [Zhang, 2016]. A study has reported TGF-b1 could induce epithelial to mesenchymal transition (EMT) in lung cancer cells [Jo et al, 2015].…”
mentioning
confidence: 99%
“…1 Clinical data display that OS occurs widely in children or teenagers under the 20 years of age. 1 Clinical data display that OS occurs widely in children or teenagers under the 20 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Local invasion and metastasis are the primary reasons for death in osteosarcoma patients [7]. Previous studies have suggested that osteosarcoma was relative higher in metastasis, with 80% of the metastases occurring in lung and the others in bone and lymph nodes [19]. Nowadays, one of the most prevalent therapies for osteosarcoma is pre-and post-operational chemotherapy combined with surgical treatment.…”
Section: Discussionmentioning
confidence: 99%